Usage of traditional complementary medicine ( TCM ) among patients with diabetes mellitus - Saidi, Sanisah (2019)
Traditional complementary medicines (TCM) have long been used to treat diabetes in Malaysia. However, the usage of TCM by the patients not often is revealed thus, the incidence of complications due to the TCM was not able to be monitored. A cross-sectional quantitative study was conducted on 105 patients with diabetes in Kuantan Pahang to determine the usage of TCM. Knowledge and attitude of the patients towards the usage of TCM were also measured using 25 items self-administered questionnaires. The data were analyzed descriptively and inferentially. Findings showed 83% of participants used TCM to treat diabetes however, the majority of them have poor knowledge (69.5%) and poor attitude (60%) towards TCM. Ninety percent (90%) admitted they concealed their usage of TCM from the healthcare professionals. A comprehensive assessment tool needs to be in place to identify the usage of TCM in order to minimize the undesirable complications and simultaneously to reduce the mortality and morbidity due to the complication of TCM.